Avaliação genética de tilápias das variedades GIFT e Saint Peter® - Machado, Luciana Maria Curty (2012)
The objectives were to evaluate the genetic parameters for the daily weight gain (GPD) of different families of Nile tilapia strain GIFT evaluated in fish farming at UEM/Codapar in Maringá and Sgarbi in Palotina, verify the occurrence of genotype-environment interaction and to compare the morphometric characteristics and performance of single sex populations of male tilapia strains GIFT® and Saint Peter reared in mixed system in Fish Culture Station of the Sgarbi, Paraná, Brazil. The cultivation was carried out during the period June to November 2011, totaling 160 days. The system used in the Fish Culture Station of the Sgarbi was a semi-intensive being adopted the density of 2.0 fish m-2. There were housed 480 fish of the GIFT strain and 1400 fish of the red hybrid, totaling 1880 animals, with an average weight of 15 g. The total GIFT population studied consisted of 720 fish, distributed in 19 families. There were used the complete pedigree information GIFT strain since its introduction in Brazil. For performance testing, two groups of fish previously identified with 240 and 480 specimens, were housed in fish farms ponds in Maringá and Palotina, respectively. The fish were distributed to have representatives of all families in both environments. After rearing period the fish assessed in Maringá and Palotina had a final weight average of 417 g and 280 g, respectively. The covariance components, genetic parameters and phenotypic were estimated proceeding to Bayesian inference, using the computer system MTGSAM. There were used the credibility interval (IC) at 5% probability to determine the differences of genetic parameters and variance components in the local culture. The additive genetic variance to the GPD showed values of 0.113 and 0.045 and the residual variance was 0.036 and 0.024, respectively for Maringá and Palotina. The phenotypic variance estimated for GPD in Maringá was higher than that Palotina. The heritability (h2) of the GPD in Maringá (h2 = 0.707) and Palotina (h2=0.575) were considered high with wide credibility intervals. The genetic correlations and phenotypic to the GPD in Maringá and Palotina had values of 0.20 and 0.13, respectively. The estimates of Spearman correlation, based on breeding values for the individual GPD (0.48) and GPD family (0.59) were significant. The estimates of the correlations of genetic parameters to GIFT strains indicate the presence of genotype-environment interaction. The daily weight gains of tilapia in local assessed are characterized as distinct, and may be influenced by different sets of genes. There were collected and individually assessed 190 and 102 tilapia males, respectively of the GIFT and Saint Peter® strains. The average final weight and daily weight gain among the three genetic groups of the GIFT strain showed no significant differences. However all groups of GIFT strain showed average values of performance and morphometric characteristics superior to hybrid strain Saint Peter®. There was a significant difference only for the height of the GIFT strain of tilapia group higher than the bottom. The morphometric characteristics and growth performance are superior to the GIFT strain, regardless of genetic group, compared to Saint Peter®, except for the head length/standard length of tilapia evaluated.